2022
DOI: 10.1002/anie.202208291
|View full text |Cite
|
Sign up to set email alerts
|

Weak Cation–Solvent Interactions in Ether‐Based Electrolytes Stabilizing Potassium‐ion Batteries

Abstract: Conventional ether-based electrolytes exhibited a low polarization voltage in potassium-ion batteries, yet suffered from ion-solvent co-intercalation phenomena in a graphite anode, inferior potassiummetal performance, and limited oxidation stability.Here, we reveal that weakening the cation-solvent interactions could suppress the co-intercalation behaviour, enhance the potassium-metal performance, and improve the oxidation stability. Consequently, the graphite anode exhibits K + intercalation behaviour (K j j … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 52 publications
1
86
0
Order By: Relevance
“…At a current density of 50 mA g –1 , the full-cell could deliver a high initial capacity of 108 mA h g –1 with a capacity retention of 80.5% after 100 cycles, and the average Coulombic efficiency is as high as 99.7% (Figure c). This result is comparable to the best performances among all reported PTCDA–graphite PIB full-cells using the concentrated electrolyte or artificial SEI film, as listed in Table S4. ,, The full-cell delivers a superior rate capability of the full-cell. The capacities are 115.1, 100.8, 96.6, 91.1, and 87.6 mA h g –1 at current densities of 20, 40, 60, 80, and 100 mA g –1 , respectively (Figure d).…”
Section: Resultssupporting
confidence: 70%
“…At a current density of 50 mA g –1 , the full-cell could deliver a high initial capacity of 108 mA h g –1 with a capacity retention of 80.5% after 100 cycles, and the average Coulombic efficiency is as high as 99.7% (Figure c). This result is comparable to the best performances among all reported PTCDA–graphite PIB full-cells using the concentrated electrolyte or artificial SEI film, as listed in Table S4. ,, The full-cell delivers a superior rate capability of the full-cell. The capacities are 115.1, 100.8, 96.6, 91.1, and 87.6 mA h g –1 at current densities of 20, 40, 60, 80, and 100 mA g –1 , respectively (Figure d).…”
Section: Resultssupporting
confidence: 70%
“…Though the PF 6 − anion could passivate Al collector, the PF 6 − anion-based electrolytes usually suffer from poor cycle stability and low coulombic efficiency (CE), stemming from their insufficient passivation ability on the anode surface and inferior oxidation-resistant properties [ 25–27 ]. The bis(fluorosulfonyl)imide (FSI − ) anion-based electrolytes generally can form an efficient passivation layer on the anode surface [ 28 31 ], but will cause corrosion on the Al collector [ 23 , 32 ] possibly due to the impurities in FSI-based salts [ 33 ]. It also has been reported that the FSI − anion could passivate Al foil effectively at certain voltages, yet corrode stainless steel components [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the electrochemical performance of electrode materials is closely related to the type of electrolyte. [49][50][51][52] Therefore, two types of electrolytes (1 M KPF 6 in diethylene glycol dimethyl ether (DEGDME) and 0.8 M KPF 6 in ethylenecarbonate (EC)/diethyl-carbonate (DEC)) are selected rst to study the cycling performance and the selected charge/ discharge curves of Bi@C composites (Fig. S4 †).…”
Section: Electrochemical Characterization Studiesmentioning
confidence: 99%